واقع إصلاح منظومة الجماعات المحلية بالجزائر في مجال تحقيق التنمية المحلية والمستدامة - بن علي, مليكة; مهاوات, لعبيدي (جامعة الوادي - University of Eloued, 2019)
إن الغرض من هذه الدراسة هو الوقوف على واقع الإصلاحات القانونية والتنظيمية للجماعات المحلية في الجزائر وأثره على تحقيق التنمية المحلية والمستدامة، من خلال التعريف بالجماعات المحلية المتمثلة في الولاية والبلدية، وتوضيح مفهوم وأهداف كل من التنمية المحلية والمستدامة، وكذا إبراز أهم الصلاحيات الممنوحة للجماعات المحلية في إطار الإصلاحات القانونية الجديدة، في سبيل تحقيقها للتنمية المحلية والمستدامة على مستوى نطاقها الجغرافي، مع ذكر أهم مقومات وآفاق التنمية المحلية والمستدامة في الجزائر وكيفية توظيفها، والكشف عن أهم الصعوبات والعوائق التي تحول دون تحقيقها، مع تقديم بعض الاقتراحات التي من شأنها المساهمة في تخطي هذه العراقيل. وقد خلصت هذه الدراسة إلى أن الجماعات المحلية وبالرغم من تمتعها بمجموعة من الإصلاحات القانونية الجديدة التي أدخلت على أنظمتها بغية مساهمتها في تحقيق تنمية محلية ومستدامة، إلا أنها بقيت تدور في حلقة الدور التقليدي المنوط بها وذلك نتيجة ضعف مواردها المالية وعدم تمتعها بالاستقلالية التامة في تسييرها نظرا لمركزية القرارات المطبقة عليها من الأجهزة الحكومية، ناهيك عن انتشار ظواهر الفساد الإداري من بيروقراطية ورشوة ومحسوبية وغيرها The purpose of this study is to examine the reality of the legal and regulatory reforms of the local communities in Algeria, and its impact on achieving local and sustainable development by: Firstly, introducing the local groups of state and municipality. Also, clarifying the concept and objectives of both local and sustainable development. Moreover, highlighting the most important powers given to local communities in the framework of new legal reforms, in order to achieve local development and sustainability at the level of their geographical scope. As well as, we mention the most important elements and perspectives of local and sustainable development in Algeria, and how to employ them. Finally, we find the most important difficulties and obstacles to achieve them, with some suggestions that would contribute to overcome these obstacles. In this study, we found that although local communities enjoyed a range of new legal reforms introduced to their systems in order to contribute to local and sustainable development, they remained in the cycle of their traditional role. This is due to the weakness of its financial resources. And, its incomplete independence. Also, the strict decisions applied by the government agencies. As well as, the spread of the phenomena of administrative corruption like bureaucracy, bribery and nepotism …..etc.
The reality of community system in Algeria in the field of local and sustainable development. the reform of the local
مقال
Keywords: الجماعات المحلية، الولاية، البلدية، التنمية المحلية، التنمية المستدامة.; Local Communities; State Municipality; Local Development; Sustainable Development